Northern exposure. Season three [videorecording (DVD)]. - Morrow, Rob; Turner, Janine, 1963-; Corbett, John, 1961-; Corbin, Barry, 1940-; Cullum, John, 1930- (Universal Studios Home Entertainment, 2013)
The cold and quirks continue in Cicely, Alaska. Includes all 23 episodes from the third season.